Legal aspect of clean water needs process - Hidayat, Rumatiga; Husein, Saddam; Suryani, Danu; Aridhayandi, M. Rendi; Suhartini, Endeh; Lukmanul Hakim, Aal; Solehudin, Ending; Handayani, Dini Oktarina Dwi (Taylor’s University, 2024)
This research aims to examine the legal aspects and the impact of the conversion of tea plantations and protected forests on clean water processing carried out in the Puncak Bogor area in Indonesia to contribute ideas about legal aspects that must be considered by processors who carry out clean water processing which includes aspects of welfare and justice, environmental impacts, and law enforcement. The research method used is an empirical juridical analysis method, namely examining legal issues arising from community activities which are the object of study. The object of study in this research is the legal symptoms that arise from water treatment activities carried out in the peak area. This research approach is normative, namely analysis using a statutory regulation approach. The results of this research indicate that the legal aspects of water treatment in the Puncak area must meet the welfare of the community following the mandate of the opening of the 1945 Constitution, and must create a sense of justice, namely not ignoring the community's need to consume clean water, paying attention to environmental aspects, namely not causing damage to the environment which results in disasters. nature, and law enforcement, namely the process of implementing laws and regulations relating to administrative sanctions and criminal sanctions. © School of Engineering, Taylor’s University.